2019
DOI: 10.3847/1538-4357/ab1b37
|View full text |Cite
|
Sign up to set email alerts
|

The Stellar CME–Flare Relation: What Do Historic Observations Reveal?

Abstract: Solar CMEs and flares have a statistically well defined relation, with more energetic X-ray flares corresponding to faster and more massive CMEs. How this relation extends to more magnetically active stars is a subject of open research. Here, we study the most probable stellar CME candidates associated with flares captured in the literature to date, all of which were observed on magnetically active stars. We use a simple CME model to derive masses and kinetic energies from observed quantities, and transform as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
103
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 155 publications
(337 reference statements)
13
103
0
1
Order By: Relevance
“…The recent observation of a CME around another star (Argiroffi et al., 2019) shows the possibilities of such measurements. However, they should be improved to have a better idea of the fluxes of particles at other stars and to validate the semiempirical laws linking flares and CME (Moschou et al., 2019). See also section 3.4.1.…”
Section: Developments Needed In Measurements and Modeling Of Atmosphementioning
confidence: 99%
“…The recent observation of a CME around another star (Argiroffi et al., 2019) shows the possibilities of such measurements. However, they should be improved to have a better idea of the fluxes of particles at other stars and to validate the semiempirical laws linking flares and CME (Moschou et al., 2019). See also section 3.4.1.…”
Section: Developments Needed In Measurements and Modeling Of Atmosphementioning
confidence: 99%
“…Every so far detected stellar CME in optical spectra had a width in wavelength of >5Å (cf. Moschou et al 2019, and references therein), which can be explained by the expansion of a CME when it is ejected (see e.g. Howard 2015; Vida et al 2019, and references therein).…”
Section: Data Preparationmentioning
confidence: 99%
“…Using the method of Xray absorptions stellar CME masses up to 10 23 g are reported (cf. Moschou et al 2019, and references therein), but the majority of those stars are no late-type main-sequence stars. The deduced minimum detectable CME masses from the S/N values are in the ranges of the stellar CMEs detected by the method of Doppler shifted emission/absorption.…”
Section: Cmesmentioning
confidence: 99%
“…While strong flares are routinely detected in active stars, particularly M-dwarfs (see Schmidt et al 2019 and references therein), recent studies have shown that the solar flare-CME paradigm might be different in the stellar regime, such that the occurrence rate of CMEs and their associated kinetic energies are reduced dramatically (Vida et al 2019, Moschou et al 2019. The recent direct detection of a stellar CME by Argiroffi et al (2019) follows the same trend.…”
Section: Introductionmentioning
confidence: 86%